“IDENTIFICATION OF DROUGHT-RESPONSIVE GENES IN SOYBEAN (GLYCINE MAX) AND GRAPEVINE (VITIS VINIFERA) VIA INTEGRATIVE RE-ANALYSIS OF MULTI-SOURCE RNA-SEQ DATA” (Scientific journal of the Fergana State University, 2026)
In this study, RNA-seq data from multiple databases were re-analysed to identify differentially expressed genes in Glycine max (soybean) and Vitis vinifera (grapevine) in response to various abiotic stresses, including cold, salinity, and drought. Using an integrative bioinformatic approach, transcriptomic datasets related to various experiments were retrieved from the NCBI database (grapevine: PRJNA787359, PRJNA549981, PRJNA788159, PRJNA763207; soybean: PRJNA852689, PRJNA933767, PRJNA813355) and combined for analysis through a standardized pipeline.Differential expression analysis (DEG) and functional annotation (GO and KEGG) revealed key genes associated with major abiotic stresses. According to the results, dozens of novel genes with altered expression in response to drought and low temperatures were identified in both species, some of which had not previously been linked to these stress types. These findings may serve as valuable genomic resources for future marker gene identification, the development of genetically modified lines, or breeding programs aimed at improving stress tolerance.